A note on scheduling on uniform parallel machines with unavailability constraints. Issue 16 (18th August 2021) - Xu, Dehua; Xu, Limin; Xu, Zhijun; Yu, Xianyu
Abstract : We show by counterexample that the binary integer quadratic programming model proposed by Kaabi and Harrath [2019. "Scheduling on Uniform Parallel Machines with Periodic Unavailability Constraints." International Journal of Production Research 57: 216–227] is incorrect. We fix this model and propose two linear ones.